DIGITAL TRANSFORMATION AND HUMAN RESOURCE LITERACY: AN ANALYSIS OF CIVIL SERVANTS’ READINESS IN IMPLEMENTING THE E-PERFORMANCE APPLICATION AT THE MAGELANG REGENCY HEALTH OFFICE - Ita Uswatun Chasanah; Raden Imam Al Hafis (Indonesian Journal of Social Sciences, Policy and Politics, 2026)
Digital transformation in Human Resource (HR) management within government institutions is a strategic mandate under Indonesia’s electronic-based governance and digital transformation policies. This study aims to analyze the readiness of Civil Servants (ASN) at the Magelang Regency Health Office in implementing the e-performance BKN application as part of national digital policy implementation. This research employs a descriptive qualitative approach using in-depth interviews, literature review, and observation for data collection. The findings reveal that digital transformation has improved transparency in performance evaluation and enhanced reporting discipline. However, ASN readiness still faces significant challenges, particularly disparities in digital literacy. Senior employees experience difficulties in operating the application’s technical features, while heavy public service workloads limit effective system utilization. In addition, inadequate infrastructure, such as unstable internet connectivity and slow server performance during peak reporting hours, further hinders implementation. As a result, the system is often used merely for administrative purposes rather than as a comprehensive performance management tool. Despite these obstacles, the e-performance BKN application has contributed to greater transparency and accountability in employee performance assessment in accordance with national regulations. The study concludes that successful digital transformation requires not only regulatory compliance but also reliable infrastructure, stable network systems, and continuous, adaptive digital literacy training for all employees.